Towards an archival study of screenplay versions: the role of screenwriting research for adaptation studies - Dagmar Brunow (Interfaces)
Archival holdings help us to better understand the collaborative process involved in screenplay development. This article mobilizes archival findings around the screenwriting process in order to contribute to recent debates within adaptation studies (Hutcheon, Bryant, Elliott, Elleström, Bruhn/Gjelsvik/Frisvold Hanssen, Stam, Rossholm). Setting out to bridge the gap between screenwriting studies and adaptation studies, this article argues that the study of screenplay versions, drafts and letters foregrounds the often overlooked artistic process involved in developing film adaptations. This article presents the case of the film adaption of Åsa-Hanna, based on the novel of the Swedish writer, journalist, suffragette, eco-critic and peace activist Elin Wägner (1882-1949) and the screenplay versions by Barbro Alving (1909-1987). It studies different script versions and ephemera at the manuscript collection at the Swedish Film Institute (Stockholm) as well as Wägner’s notebooks, drafts and letters at KvinnSam (Göteborg). The aim of this article is twofold: first, to contribute to adaptation studies by highlighting the role of the screenplay and the process of screenwriting in the process of transmediation. Second, to stress the importance of the industrial context of film production and distribution for adaptation studies.